Radiological imaging findings of the hepatic tuberculosis - Koc, Mustafa (My University, 2021)
This study aims to investigate the radiological findings of hepatic tuberculosis. Imaging findings of 8 patients diagnosed with biopsy-proven hepatic tuberculosis from January 2015 to March 2021 were retrospectively reviewed. The diagnosis of these cases was confirmed by ultrasound-guided biopsy. The patients were between the ages of 24-72. Four patients had only parenchymal tuberculosis and eight patients had mixed parenchymal and bile duct involvement. Parenchymal tuberculosis patients showed hypoechoic nodules in Ultrasonography (US). In Computed Tomography (CT), poorly contrasted hypodense nodules with central calcification adjacent dilated intrahepatic ducts were seen. Magnetic Resonance Imaging (MRI) findings were correlated with CT. Most patients had more than one lesion. Two patients with a single lesion. The sizes of the lesions varied between 0.5 and 6 cm. Seven patients with bile duct involvement showed hilar stenosis involving the intrahepatic ducts and common bile duct. Parenchymal atrophy was seen in 5 patients. Pulmonary and other organ involvement of tuberculosis was seen in 5 patients. In conclusion, Hepatic tuberculosis should be kept in mind multiple lesions in the liver, including calcification, accompanied by atrophy and bile duct enlargement especially in the presence of active pulmonary tuberculosis.
Keywords: Genel ve Dahili Tıp; Patoloji; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme